Reduction in ins-7 gene expression in non-neuronal cells of high glucose exposed Caenorhabditis elegans protects from reactive metabolites, preserves neuronal structure and head motility, and prolongs lifespan - Mendler, Michael; Riedinger, Christin; Schlotterer, Andrea; Volk, Nadine; Fleming, Thomas; Herzig, Stephan; Nawroth, Peter Paul; Morcos, Michael (Journal of diabetes and its complications, 2017)
Background: Glucose derived metabolism generates reactive metabolites affecting the neuronal system and lifespan in C. elegans. Here, the role of the insulin homologue ins-7 and its downstream effectors in the generation of high glucose induced neuronal damage and shortening of lifespan was studied. Results: In C. elegans high glucose conditions induced the expression of the insulin homologue ins-7. Abrogating ins-7 under high glucose conditions in non-neuronal cells decreased reactive oxygen species (ROS)-formation and accumulation of methylglyoxal derived advanced glycation endproducts (AGEs), prevented structural neuronal damage and normalised head motility and lifespan. The restoration of lifespan by decreased ins-7 expression was dependent on the concerted action of sod-3 and glod-4 coding for the homologues of iron-manganese superoxide dismutase and glyoxalase 1, respectively. Conclusions: Under high glucose conditions mitochondria-mediated oxidative stress and glycation are downstream targets of ins-7. This impairs the neuronal system and longevity via a non-neuronal/neuronal crosstalk by affecting sod-3 and glod-4, thus giving further insight into the pathophysiology of diabetic complications.